æ±‰è¯è¶‹å‘è¡¥è¯â€œæ¥â€å’Œâ€œåŽ»â€çš„ä½¿ç”¨åè¯¯åˆ†æžâ€”ä»¥ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦ å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±Šå¦ç”Ÿä¸ºä¾‹ - Dayana, Hilaria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe adverb of direction is the word positioned next to a verb or adjective which shows the object?s movement or movement adverb. In Chinese, adverb of direction sits on the highest rank, especially ?Lai? and ?Qu? where we found used in conversation on a daily basis. As part of a simple adverb, these two words tend to be erroneously used by College and University Students on how to use them, the rank, and object?s position.The writer did a research on Chinese Language Students of Tanjungpura University of the year 2015 about the use of adverb of direction ?Lai? and ?Qu?. According to the data collected, writer analysed the mistakes on how the students use those two words. The writer concluded the Students mistake percentage on using the adverb ?Lai? and ?Qu? is 50.51% and 49.90%. The mistakes found are the words they chose and the words' construction. The mistakes are influenced by the native language and foreign language they learned.Keyword: Adverb of Direction ?Lai? and ?Qu? Error Analysis